A safety assessment of crizotinib in the treatment of ALK-positive NSCLC patients. (March 2015) - Dikopf, Alana; Wood, Kevin; Salgia, Ravi
<x xml:space="preserve">Abstract</x> Introduction: In the past decade, the treatment of NSCLC has been revolutionized by the discovery of key oncogenic driver mutations and the therapies that specifically target these mutations. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Crizotinib&logicalOpe1=OR&field2=articletitle&text2=Crizotinib&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Crizotinib has been shown to be an inhibitor of MET, anaplastic lymphoma kinase (ALK) and ROS1 receptor tyrosine kinases, and is FDA approved for ALK inhibition. Crizotinib is effective in NSCLC that harbors ALK translocations resulting in overexpression of oncogenic ALK fusion proteins. Areas covered: This paper will review crizotinib as a treatment for ALK-positive NSCLC. It will discuss the drug's adverse events, drug–drug interactions and other important clinical and safety information related to crizotinib. Expert opinion: Compared to standard chemotherapy, crizotinib shows improved progression-free survival in ALK-positive NSCLC, with patient's reporting improved quality of life. However, certain adverse events are more frequent with crizotinib versus standard chemotherapy and must be monitored for closely. The most common adverse events include ocular and gastrointestinal disturbances, cardiac and endocrine abnormalities, and peripheral edema. Many, though not all, of these side effects are likely due to the multiple tyrosine kinases inhibited by crizotinib, and will likely improve with second- and third-generation inhibitors that inhibit ALK more specifically.